The LORONG: transforming gesture and structure in a shapeshifting student recreation alley / Juliza Mohamad ... [et al.] - Mohamad, Juliza; Hanafi, Nik Nurul Hana; Anuar, Nor Hafizah; Abu, Muhammad Firdaus; Shakeer Alias, Mohammad Amirul; Saiful Bahri, Ahmad Baihaqi (Universiti Teknologi MARA, Kedah, 2023)
The LORONG is an innovative project that aims to transform the conventional concept of student recreation alleys. These spaces often lack creativity and fail to fully engage students, resulting in a need for a fresh and novel approach. The project addresses this gap by reimagining recreation alleys as dynamic environments that foster community and inspire creativity. The primary objective of The LORONG is to redefine the student recreation alley by incorporating elements of shapeshifting, gesture, and structure. This groundbreaking design concept allows the alley to adapt and transform to accommodate various leisure activities and moods. By integrating these innovative features, The LORONG enhances the overall experience for students, encouraging social interaction, artistic expression, and academic engagement. By revitalizing student recreation spaces, it creates a vibrant and inclusive environment that promotes student well-being and happiness. The dynamic atmosphere of The LORONG fosters social interaction, diversity, and cultural exchange, contributing to the overall sense of community within the campus. Additionally, the project provides opportunities for students to explore their artistic talents and engage in recreational activities, enriching their college experience. Furthermore, The LORONG holds significant commercialization potential. Its unique design and transformative features make it an appealing concept for universities and educational institutions seeking to enhance their student recreational facilities. The LORONG represents a revolutionary approach to student recreation alleys. Its shapeshifting design, incorporating elements of gesture and structure, creates an immersive and adaptable space for students to socialize, relax, and engage in various activities. The project brings forth benefits to society by promoting student well-being, fostering community, and offering commercialization potential. The LORONG sets a new standard for student recreation spaces, inspiring creativity and providing a dynamic environment for students to thrive.